Protective effects of paederoside in rotenone-induced cellular models of Parkinson’s disease - Lang, Juan; Xiong, Zhongkui (Frontiers in Cell and Developmental Biology, 2025)
IntroductionParkinson’s disease (PD) is the most prevalent age-related neurodegenerative motor disorder. It affects approximately 1% of individuals aged 65 and older, with its prevalence increasing significantly with advancing age. Current therapeutic approaches primarily focus on symptom management and modestly slowing disease progression, while definitive interventions capable of halting or reversing neurodegeneration remain unavailable. Emerging studies suggest that misfolded proteins progressively accumulate in the neurodegenerating brain, partially attributable to elevated levels of reactive oxygen species and reactive nitrogen species (RNS). The RNS family includes various nitrogen-based compounds, such as nitric oxide (NO), nitroxyl derivatives, and S-nitrosothiol modifications. Phytochemicals have attracted considerable scientific interest as promising candidates for disease-modifying therapies. Prior studies have shown that paederosidic acid, extracted from P. scandens (Lour.) Merrill, exhibits notable neuroprotective properties in rodent models. However, the potential of paederoside to confer protection in PD cellular models remains unexplored.MethodsPaederoside, a bioactive compound isolated from Paederia (Rubiaceae family), including Paederia foetida and Paederia scandens, was evaluated using rotenone-challenged Neuro-2A (N2A) cells and BV-2 microglial cultures, which served as experimental models of PD pathology. Catalpol was used as a comparative pharmacological reference.ResultsIn this study, both paederoside and paederosidic acid methyl ester (PAME) significantly reduced NO accumulation in rotenone-induced N2A and BV-2 cells. Paederoside induced a dose-dependent reduction in inducible nitric oxide synthase (iNOS) activity in the rotenone-treated BV-2 cells. When the nuclear factor-κB (NF-κB) inhibitor BAY11-7082 was added 2 h before rotenone exposure, no statistically significant difference in NO levels was observed between the paederoside-treated and untreated groups. Pretreatment with 1 μM or 10 μM of paederoside significantly attenuated the formation of nitrated α-synuclein (α-Syn) in response to rotenone exposure. Furthermore, pretreatment with 10 μM paederoside markedly enhanced cell viability in rotenone-treated N2A cells.DiscusionIn summary, these findings demonstrate the neuroprotective potential of paederoside through modulation of the NF-κB/NOS/NO/nitrated α-Syn nitration signaling pathway.